Reconfiguração da rede de distribuição inteligente usando recozimento simulado - Amorim, João Ricardo Barreto de Carvalho (2022)
This work proposes an Electrical Energy Distribution Smart Reconfiguration method using the Simulated Annealing methaheuristic. It has been implemented two new classes in the C# language, the first to caracterize the Simulated Annealing algorithm parameters, and the second one to make the interface between the implemented methaheuristic and the coupling with the OpenDSS software, wich is a distribution systems power flow simulator. To this work, will be utilized the integrated denvelopment ambient of Visual Studio 2019. The algorithm was implemented in an interface devenloped to provide an agile and dinamical parameters modification. The algorithm will be validated in a 5 bus system and tested in both 33 and 69 buses, well used in the literature. The tests results suggests that the proposed algorithm reaches the intended outcomes and solutions in an efficient, fast and precisely.